Determination of Proximate Composition and Sensory Attributes of Scallop (Flexopecten glaber) Gonads - Nermin Berik; Ekrem Cem Çankırılıgil (Marine Science and Technology Bulletin, 2013)
In this study, edible properties of gonads belonging to Flexopecten glaber, a particular Mediterranean species, were determined. The scallops used in the assay were purchased from Canakkale fish market, which were collected in Lapseki Bay in Canakkale. Sampling was done in February and April. The study was conducted in order to determinate proximate composition and sensory attributes of scallop gonads. Meat yield averages of scallop gonads were higher in April than in February (P≤0.05). Minerals that cause health risks such as Al, Pb, Cd were also determined and found below the legal limits in scallop gonads. Furthermore, results of microbiological analyses showed that values of microorganisms that cause health risks were also below the legal limits in scallop gonads. According to the sensory appreciation test in cooked gonads, fried gonads had the highest score. Eventually, it can be suggested that scallop gonads are appropriate food sources in terms of nutritional values and sensory attributes. This study will lead both sector employees and consumers about edible properties of Flexopecten glaber’s gonads and this will also increase the contribution of fishery products in sector and economy.